Bibliometric Insight into Artificial Intelligence Application in Investment - M.K. Sarjas; G. Velmurugan (International Journal of Computational and Experimental Science and Engineering, 2025)
This study explores the key trends and ideas around using artificial intelligence in investment. The authors employ the bibliometric approach, using VOS viewer software to analyze 582 academic articles from the SCOPUS database between 2004 and 2023. The findings show that interest in artificial intelligence within investment has grown since 2017, reflecting a delay in its adoption by the investment industry. China, the United States, India, and the United Kingdom were identified as the leading countries researching this topic. The National Research University Higher School of Economics, Russia, and Spiru Haret University, Romania emerged as the most active institution in this area. It highlights the growing adoption of AI across various financial institutions, including banks, hedge funds, and fintech firms, due to its ability to analyze extensive datasets, enhance decision-making, and optimize portfolios. Key AI-driven, cost-effective investment advice. These technologies outperform traditional advisors’ inefficiency and objectivity but face challenges in gaining trust among seasonal investors. However, the study has limitations, as it only used articles from the SCOPUS database and focused solely on English–language publications. The future directions emphasize the integration of AI with sustainability and natural language processing, reflecting its potential to address broader societal challenges. The study underlines that extensive regulatory frameworks, improved collaboration, and user-centric AI solutions are required to optimize its influence on investment practices.